Soil Stabilization Method By Using Natural Bamboo Fibre - Dasthagir, Nur Hidayah (Universiti Sains Malaysia, 2022)
Bamboo is one of the fastest growing plants in the world, with species ranging in size from a few centimeters to inches tall. Bamboo is a unique plant that can reach its full height of up to 30m in 2 to 4 months. Despite the fact that bamboo has been used as a construction material for thousands of years, there have been few studies on the mechanical properties of the bamboo itself in Malaysia. Bamboo has been identified as a potential natural reinforcing material for soil improvement and stabilization. The shear strength behaviour and compression strength of a bamboo fibre reinforced soil are investigated through the systematic literature review sysnthesis. The literature review shows that increasing the percentage of fibre in the soil increases the shear strength parameters to an optimum level for construction purposes. When two different lengths of fibre are considered in the study, shear strength and compression strength parameters increase as the length of the fibre increases. It was revealed that the cracked area ratio decreased by increasing of the added amount of the fibre reinforcing material regardless of that type and species. In particular, it was reported that the effect of soil suppressing failure was remarkable in the additional of the bamboo fiber with long fiber length, which the author examined the availability of the bamboo fibre to improve the soil stabilization and as a result, it was revealed that the specimens mixed with the bamboo fibre had high erosion resistance and better shear and compressive strength compared to other conventional method. With the available data on bamboo properties, structural engineers should consider bamboo as a construction material in modern engineered buildings, in addition to a soil stabilizing method for construction.